Mulches application and shading to improve tuber yield of shallot (Allium ascalonicum L.) Cv. Palu - Bahrudin Bahrudin; Syekhfani Syekhfani; T. Wardiyati; M. Santoso (The Indonesian Green Technology Journal, 2012)
Optimal growth environment particularly solar radiation intensity and temperature are the important factors to reach maximum yield of shallot crop. The average production of shallot at central Sulawasi about 4.3 ton ha-1,  it is below the national production (8.8 ton ha-1) (Board of Statistic Center, 2000). It is the reason to improve agrotechnology to get the best yield of the Palu local cultivar. The objective of this research is to evaluate effects of shading level and mulches on growth and tuber yield of shallot.  The research was conducted on a low altitude, 20 meters above sea level, Sidera district, Sigi Biromaru, Donggala regency.  The average temperature of the area is 34 -37°C during day and 22 – 23.2ºC during night, with the relative humidity 71 – 77%.   The field experiment on  environmental modification  using polynet shading and mulches was arranged in the Randomized Complete Block Design with two factors: (1) mulches application: without mulch, black silvery plastic mulch; and (2) Polynet shading: without shading, 30 % shading and  60 % shading. Results of experiment suggest that application the black silvery plastic mulch  and 30 % shading produced bulb fresh weight  1.048 kg/m2 equal to 10.48 tons ha-1, it is higher then the control treatment which produces 0.453 kg/m2 equal to 4.53 tons ha-1. Key words: mulches, shading, shallot.